Improving the criteria-based evaluation assessment for master’s research in engineering programs - I. A. Chekardovskaya; S. M. Chekardovskiy; M. N. Chekardovskiy (Архитектура, строительство, транспорт)
This study aimed to improve the methodology for evaluating the research activities of engineering master’s students. Criterion-based evaluation is one of the main tools for assessing the development of research competences. Based on data from professional experts and relevant regulatory documents, evaluation criteria for student research were defined. Parameters for a credit-based evaluation system were introduced. The methodology proposed for calculating a composite research assessment provides a holistic and objective evaluation of the research conducted, independent of the opinions of supervisors or individuals.